Neonatal tetanus in Kano - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Neonatal tetanus (NNT) is one of the childhood's preventable diseases and a leading cause of neonatal death especially in developing countries. It is entirely preventable through effective immunisation of women of child-bearing age, and through simple and basic precautionary measures in child delivery.Objective:This study highlighted the burden of neonatal tetanus in Kano over a period of ten years.Materials and Methods:We retrospectively studied the case notes of neonatal tetanus admitted over a ten-year period (2000-2009). The records of neonates admitted as cases of neonatal tetanus into the special care baby unit of Aminu Kano Teaching Hospital, a tertiary health facility in Kano, northern Nigeria, over a ten-year period were reviewed. Data on age at presentation, local government area from which the neonates presented, antenatal history, maternal immunisation status, clinical feature, complications and the outcome were noted.Results: Majority of the cases (74%) were concentrated in the cosmopolitan areas of Kano. Only 33% of the mothers had antenatal care (ANC) while only 18 (24%) of the mothers received immunisation against tetanus. In all, 76% of the mothers delivered outside the medical facility. The umbilical cord was the route of infection in 52.7% of cases. The case-specific fatality rate was 51.4%.Conclusion:The incidence of NNT is still very high in Kano and this scourge can be tackled through improved quality and accessibility of ANC services and tetanus toxoid (TT) vaccination, provision of skilled attendants at delivery under hygienic conditions and avoidance of harmful traditional practices.